TIPOLOGI PENDAYAGUNAAN KOTORAN SAPI DALAM UPAYA MENDUKUNG PERTANIAN ORGANIK DI DESA SUMBERSARI KECAMATAN PONCOKUSUMO KABUPATEN MALANG - Moch. Agus Krisno Budiyanto (Jurnal Gamma, 2011)
Moch. Agus Krisno BudiyantoStaf Pengajar Jurusan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah MalangAlamat Korespondensi : Jl. Cengger Ayam Dalam I/38 MalangEmail: aguskrisno@yahoo.co.idABSTRACTOrganic farming is an alternative to the development of eco-friendly farming and sustainable.Organic farming is one attempt to win the competition in the market seized on post-Asean freetrade. This research addresses the concept of “Typology Administrative Cow Manure in OrganicFarming Support Efforts in the Sumbersari District Poncokusumo Village Malang Regency.” Thisconcept is expected to enrich the lecture material of General Microbiology, Introduction toMicrobiology Subject Agriculture and Industry.The research approach used in this study is a qualitative research design with phenomenologyresearch. Research informants are cattle breeders, farmers, and Owners / Investors Cow in theSumbersari District Poncokusumo Village Malang Regency. Sampling technique used was purposivesampling. Data collection methods used are indepth interviews and questionnaires. The researchdata were analyzed with qualitative analysis (Content Analysis) with Interactive Models by Millesand Hubermen (1994).Based on research results can be stated that the majority of farmers utilize manure as organicfertilizer (cow dung by piling soil or put holes) and some small farmers dispose of cow manure thatpollute the environment just a place to stay, even some farmers who let the dirt at times cow barnbecame so bad environmental sanitation that can affect the health of cattle. The use of organicmanure fertilizer is also increasing with the reason it easier to find, cheap, and better fertilizationresultsKey Word: administrative, cow manure, organic farming, organic fertilizer, fertilization results